Parenting your parents : support strategies for meeting the challenge of aging in the family - Mindszenthy, Bart J., 1946- (Dundurn Group, 2005)
When our parents reach a certain age and have difficulty coping, we find ourselves wondering how to provide them with the kind of love, care, support, and attention they need - just as they have done for us all our lives. Parenting Your Parents shows, through case studies, that you are not alone and offers advice to help you along this difficult but rewarding journey. This revised and updated edition of the 2001 bestseller features a new introduction, new case studies, an expanded Personal Parenting Planner, and a totally updated resource directory. With reflections and advice from one of Ca.